Two-level Path Authentication in EPCglobal Network - WANG, Hongbing (Institutional Knowledge at Singapore Management University, 2012)
In this paper, we propose a two-level path authentication protocol for object genuineness verification in RFID-based supply chain and EPCglobal Network. In our solution, a tag's path in a supply chain can be generated dynamically, where each reader in the path can verify the validation of the path using its own private key. Our solution has a few promising properties, including dynamic path generation, distributed authentication, and scalability. In comparison, the previous path authentication solution for RFID tags is focused on static path generation and centralized control. The efficiency of our path authentication protocol is enhanced significantly by dividing a whole path into multiple segments according to organization structures. The security and privacy of our protocol are established based on two cryptographic primitives, hierarchical identity-based encryption and batch verification signature.